A case of Cardiocondyla aural parasitosis in Middle East Refugee Camp: insect removal in resource poor environment - Cuthbert, David; Nayal, Wasan; Cuthbert, Darren; Kalczynski, Jeffrey; Khan, Mansoor (Journal of Global Medicine, 2024)
We present a case of successful removal of aural foreign bodies from the external otic canal. In this scenario, the foreign bodies were an uncommon insect, the Cardiocondyla. The Cardiocondyla species is within the family Formicidae, otherwise known as the ant. The patient was seen in a remote location, a refugee camp in Jerash, Jordan, with limited resource accessibility. The insects and all aural foreign body contents were successfully debrided with gentle irrigation. This case presents the opportunity to evaluate an alternative insect removal technique when resources are not available. It also reviews the classic recommended techniques, assesses the risks and sequela of retrieval, and appraises the threat of formicidae exposure in the wild.